ANALYSIS OF FACTORS RELATED TO OUTPATIENT WAITING TIME AND PATIENT SATISFACTION OF MOBILE JKN USERS USING THE SERVPERF AND IPA METHODS AT MUHAMMADIYAH GENERAL HOSPITAL, NORTH SUMATRA - Gurning, Fitriani Pramita; Salsabila Br. Sitepu, Dhea; Syafira, Listi Tri (HEARTY, 2026)
The Ministry of Health sets a maximum patient waiting time standard of 60 minutes for outpatient services, as stated in the Decree of the Minister of Health Number 129/Menkes/SK/II/2008 concerning Minimum Service Standards (SPM) for Hospitals. This standard covers the time from when a patient registers until they are served by a doctor. This study aims to analyze factors related to outpatient waiting time and the level of patient satisfaction of the Mobile JKN application users at Muhammadiyah General Hospital, North Sumatra. The research method used is quantitative with a cross-sectional design, with a sample of 96 respondents selected using the Lemeshow formula. Measurement of service quality is carried out using the SERVPERF method and Importance Performance Analysis (IPA) analysis to assess the suitability between patient expectations and reality regarding the services received The results of the study showed that the average value of service quality conformity was 90.23%, which is included in the fairly good category. The Assurance dimension had the highest conformity value of 92.10%, while the Empathy dimension showed the lowest conformity value of 87.05%. Factors significantly related to patient satisfaction include the number of medical personnel, the registration system, and service infrastructure, which have a positive effect on accelerating waiting times and increasing perceptions of service quality. In conclusion, outpatient services at Muhammadiyah General Hospital, North Sumatra have been running well, but need to be improved in the aspects of empathy and reliability of medical personnel as well as optimization of the digital queue system to achieve more optimal patient satisfaction.